Salmonellosis: lessons drawn from a germ-free pig model - Trebichavský, I; Schulze, J; Dlabac, V; Cukrowska, B; Tlaskalová-Hogenová, H; Reháková, Z (Folia microbiologica, 1998)
The germ-free pig model is shown to be useful for studying salmonellosis. The immune status of germ-free and infected gnotobiotic piglets is described. The regulatory role of cytokine is discussed and compared with our experimental findings.
Keywords: prasata; organismy bez specifických patogenů; Swine; modely nemocí na zvířatech; Immunoglobulin G; Specific Pathogen-Free Organisms; Interferon-gamma; Tumor Necrosis Factor-alpha; Immunoglobulin M; imunoglobulin M; B-lymfocyty; imunoglobulin G; interferon gama; salmonelová infekce u zvířat; Salmonella Infections, Animal; Animals; zvířata; Disease Models, Animal; imunoglobulin A; protilátky bakteriální; Salmonella typhimurium; TNF-alfa; B-Lymphocytes; Immunoglobulin A; Antibodies, Bacterial